Juridical Analysis Of Land Allocation In Forest Areas Over BP Batam's Management Rights On Rempang Island - Sitti Isramira Pratiwi; Markus Gunawan; M. Soerya Respationo; Erniyanti Erniyanti (International Journal of Humanities and Social Sciences Reviews, 2024)
The incident of residents on Rempang Island rejecting the development of the Rempang Eco-city Project certainly raises many questions for the general public in viewing this problem. With the publication of Coordinating Ministerial Decree Number 7 of 2023 concerning the Third Amendment to Coordinating Ministerial Decree Number 7 of 2021 concerning Amendments to the List of National Strategic Projects, the public is in the spotlight to find out what processes and laws and regulations regulate each process and stage. To study this in more depth, it is necessary to carry out a Juridical Analysis of the Allocation of land in Forest Areas above BP Batam's Management Rights on Rempang Island to be able to find out the legal arrangements, implementation, obstacles and solutions for allocating land in forest areas above BP Batam's Management Rights on the Island. Eccentric. The research method used is a normative and juridical approach, which focuses on doctrinal legal research and refers to legal norms contained in applicable laws and regulations as a normative basis, so this research emphasizes secondary data sources, both in the form of theories- legal theory and through interviews with sources or parties related to the problems to be researched above. All data obtained is then processed, analyzed and interpreted logically, systematically using deductive methods. The results of research on the allocation of land in forest areas above BP Batam's Management Rights on Rempang Island based on applicable laws and regulations are not justified and BP Batam will not be able to use and utilize all or part of its land either for its own use or in collaboration with other parties because BP Batam's authority as the holder of Management Rights will only arise after the issuance of a Management Rights Certificate from the Batam City National Land Agency Office, it is not permitted to carry out new development and development in forest areas before changes to the designation and function of forest areas are made, and if it is on land that will be granted Rights Management still has land/buildings/plants belonging to the people, so compensation for losses and relocation of residents to new residential areas must be carried out first on the basis of deliberation. The author hopes that from the research that has been carried out, the government can create legal products that create a sense of justice for society and can turn the results of this research into useful knowledge for parties facing similar legal problems.